Effects of SGLT-2 inhibitors on renin-angiotensin-aldosterone system and their correlation with glucose metabolism in type 2 diabetes mellitus patients with hypertension: A prospective study - Ningning Wang; Junfeng Kong; Ziming Lu; Fei Cao; Erjun Tian; Junhui Li; Shutong Li; Shuai Liu; Baohong Yue (PLoS ONE, 2025)
Background The impact of sodium-glucose cotransporter-2 inhibitors (SGLT-2is), including dapagliflozin, on the renin-angiotensin-aldosterone system (RAAS) in type 2 diabetes mellitus (T2DM) patients remains controversial, as they may either activate or inhibit RAAS, subsequently influencing glucose metabolism and the accuracy of the aldosterone-to-renin ratio (ARR) in diagnosing primary aldosteronism (PA). However, the effects of SGLT-2is therapy on RAAS and their correlation with glucose metabolism have not been well studied. Methods A cohort of 147 patients with T2DM and hypertension was prospectively recruited and categorized into two groups: diabetic kidney disease group (DKD, n = 73) and non-DKD group (n = 74), based on diagnostic criteria for diabetic complications. Patients were prescribed 10 mg dapagliflozin daily for 3 months. The primary outcome measure was the change in renin (REN) levels during outpatient visits at baseline, 1 month, and 3 months. The secondary outcome was the change in other metabolic biomarkers from baseline to the 3-month visit. To evaluate the relationship between RAAS components and various glucose metabolism indicators, including HbA1c, FBG, CP, HOMA-β, HOMA-IR, and UACR, Spearman correlation and multiple linear regression analyses were conducted at baseline and 3-month visit. Results After 3 months, the BMI, HbA1c, FBG, TG, TCHO, SBP, DBP, UACR, and HOMA-IR levels were significantly decreased, while Crea and HOMA-β were significantly increased from the baseline in both groups. Additionally, the differences from the baseline in FBG (−2.64 ± 2.66 vs. −1.70 ± 1.92 mmol/L) and UACR (−355.01 ± 1534.12 vs. −4.66 ± 7.86 mg/g) values were significantly higher in DKD group than those in non-DKD group. REN levels increased significantly from baseline at 1-month visit (4.15 ± 7.35 vs. 2.75 ± 8.03 ng/L; DKD vs. non-DKD; between-group difference, p < 0.05), while ARR values decreased significantly from baseline at 1-month visit (−0.70 ± 1.16 vs. −0.59 ± 1.19; between‑group difference, p > 0.05) and 3-month visit (−0.45 ± 1.15 vs. −0.42 ± 1.07; between‑group difference, p > 0.05) in both groups (within‑group change vs. baseline, p < 0.017). Interestingly, no temporal differences were observed in ALD levels. REN levels returned to baseline after three months of treatment; yet the ARR, which was primarily influenced by REN, remained below its initial value. Multiple linear regression analysis revealed that a 100% increase in Log-ALD was associated with a 0.143 nmol/L higher CP and a 15.8% higher HOMA-IR in DKD group( p < 0.05). A 100% increase in Log-REN was associated with a 0.359 mg/g lower UACR in DKD group and a 0.042 mmol/L higher FBG in non-DKD group( p < 0.01). These correlations were independent of the internal interactions of RAAS but were significantly attenuated after 3 months of treatment. Conclusions The correlations between RAAS markers and glucose metabolism indices were significantly attenuated, potentially due to lowered blood glucose levels after SGLT‑2is treatment. However, it is noteworthy that short-term therapy may elevate REN levels and reduce ARR, potentially resulting in false-negative outcomes in PA screening.